PENGEMBANGAN BUKU CERITA BERGAMBAR PADA MATERI KEBERAGAMAN KARAKTERISTIK UNTUK MENINGKATKAN MINAT BACA SISWA KELAS III SEKOLAH DASAR - Sunarti; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This researcher is motivated by the low interest in reading students in learning in the PPKn subject class on the material of characteristic diversity. learning media in schools still use conventional media such as textbooks with lecture methods so that students become less interested in reading. the unavailability of learning media, especially in PPKn subjects on the material of characteristic diversity. This research uses research and development (R&D) methods using the ADDIE model. The model consists of five stages, namely: analysis, design, development, implementation, and evaluation. The subjects used with the research consisted of three validators (material experts, linguists, media experts), teachers and students. The data collection techniques used were observation, interview, questionnaire and documentation. Data analysis in the study in the form of quantitative data obtained from the results of responses, suggestions from experts and teachers as well as based on the results of observations and interviews presented in descriptive form and quantitative data obtained from the results of expert validation questionnaires, teacher and student responses into numbers and interpreted with assessment criteria for product feasibility. The results of this study are picture storybook media that have been declared very valid by experts with an overall average value of 89.16% with very valid criteria and an average percentage of 91.76% with very practical criteria, and its effectiveness obtained an average value of 89.1% with very effective criteria. The illustrated storybook media developed is very valid, practical and effective for increasing students' interest in reading in the subject of Pancasila and civic education (PPKn) material on the diversity of characteristics.